Reconstruction Under Fire Case Studies and Further Analysis of Civil Requirements - Stearns Lawson, Brooke (RAND Corporation, 2010)
Building on a framework for integrating civil and military counterinsurgency (COIN) first presented in prior RAND research, this volume presents an approach to the civil component of counterinsurgency that builds on detailed background, context analysis, and threat analysis to identify and develop critical civil COIN activities and illustrates them with three case studies from Afghanistan, Iraq, and the Democratic Republic of the Congo.